Pengaruh Harga, dan Kualitas Produk Shopee Terhadap Keputusan Pembelian Konsumen - Moses Abiezer; Harry Sardjono (UNIVERSITAS KALBIS, 2022)
This research aims to determine the influence of price and quality of products Shopee against consumer buying decisions. There are three variables in this study which include price, product quality, and consumer purchase decision. Researchers use quantitative methods and samples used in this study amounted to 112 respodenden that knew e-commerce shopee. The technique used in this study is purposive sampling which is part of the non-probability sampling. The research Data being adopted using SPSS 20 indicates that the variable price and product quality have an influence on purchasing decisions